Demotivation of Second Semester Art and Religion Faculty Students in Learning English Language (IAKN Ambon) - thobias sarbunan (STKIP CITRA BAKTI, 2021)
This research is aimed to describe demotivation factors which abundant on the level of Maluku university students in learning the English language. In the methodology section, the researcher used descriptive methodology, which sample was twenty-five students on second-semester church and religion department who enrolled in the English language in the second semester. The researcher was collect the data from the accomplishment of student’s discovery learning tasks; constructed of footage data of both responses and participation to the online teaching and learning on chatting group of English language class, email database of the second-semester opinion’s in learning the English language, and also the participation in online teaching through live streaming on Facebook. In conclusion, those factors which compulsory in English language learners were influence by intrinsic motivation.